2001
DOI: 10.1002/ccd.1209
|View full text |Cite
|
Sign up to set email alerts
|

Use of the new IntraStent for treatment of transverse arch hypoplasia/coarctation of the aorta

Abstract: We report the use of a new biliary stent (IntraStent Double Strut LD) adapted for use in a 16-year-old young man with moderate-severe transverse arch hypoplasia/coarctation of the aorta following two surgical attempts at correction/relief of the coarctation. The stent implantation procedure resulted in complete relief of the coarctation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…There were no deaths, and there were significant improvements in transverse arch dimensions with reduction in gradients across the stented portion of the transverse arch. This is in keeping with other previous smaller series [].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There were no deaths, and there were significant improvements in transverse arch dimensions with reduction in gradients across the stented portion of the transverse arch. This is in keeping with other previous smaller series [].…”
Section: Discussionsupporting
confidence: 93%
“…Residual hypoplasia of the transverse arch may persist after surgery [], although this may reduce with the increasing use of an extended arch repair approach in neonates and infants . Residual arch hypoplasia has been shown to cause obstruction of the arch with resulting hypertension [].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the long-term result still needs to be clarified, follow-up catheterization showed that rate of re-stenosis and percent stenosis remained relatively low after intervention. However, dilatation over 14 mm, the normal typical pulmonary artery size of an adult, is potentially harmful to the vessel when using over a 12 Fr sheath for delivering a bulky stent such as the Palmaz® genesis stent (Johnson & Johnson-Cordis, Bridgewater, NJ, USA) 10)11)15)…”
Section: Discussionmentioning
confidence: 99%
“…That is not because of questions concerning its effectiveness and safety, but because of lack of interest among government and companies 10-12). Although few studies had demonstrated a high success rate after 20 years of experience, there has not been any multicenter-randomized controlled study 9)13)14).…”
Section: Introductionmentioning
confidence: 99%